2023
DOI: 10.1186/s12958-023-01089-3
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-borne microRNA-34c regulates maternal mRNA degradation and preimplantation embryonic development in mice

Abstract: Background Studies have shown that sperm-borne microRNAs (miRNAs) are involved in mammalian preimplantation embryonic development. In humans, spermatozoan miR-34c levels are correlated with in vitro fertilization outcomes, such as embryo quality and the clinical pregnancy and live birth rates. In rabbits and cows, miR-34c improves the developmental competence of embryos generated by somatic cell nuclear transfer. However, the mechanisms underlying the regulation of embryonic development by miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Interestingly, miR-34b/c levels in sperm were only associated with a decrease in miscarriages, and increased implantation and pregnancy rates at certain Ct thresholds, determined using receiver operating characteristic curve (ROC) analysis [ 171 ]. Mechanistically, miR-34c-related improvements to pre-implantation embryo development appear to be stage-dependent and occur through diverse biological processes [ 172 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, miR-34b/c levels in sperm were only associated with a decrease in miscarriages, and increased implantation and pregnancy rates at certain Ct thresholds, determined using receiver operating characteristic curve (ROC) analysis [ 171 ]. Mechanistically, miR-34c-related improvements to pre-implantation embryo development appear to be stage-dependent and occur through diverse biological processes [ 172 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that AR expression is critical for Sertoli cell maturation, blood-testis-barrier (BTB) formation and maintenance, germ cell proliferation and differentiation, THC-induced reduction in miR-346 transcripts may also explain the association between cannabis use and lower sperm counts [ 177 ]. Considering that the contribution and abundance of sperm-borne miRs during pre-implantation embryo development are stage-dependent [ 172 ], it is possible that we found no significant differences in the abundance of miRs-324, and -34c in blastocysts generated from THC-treated sperm because we quantified miRs only at the blastocyst stage. Although we analyzed RNA from whole blastocysts, differentially expressed genes predictive of pregnancy success appear to be more abundant within the TE compared to the ICM in human blastocysts [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of human and other mammalian spermatozoa have found that concentrations of specific mRNAs and miRNAs are correlated with fertility and the growth of the offspring (Hamatani, 2012;Hamilton et al, 2022;Joshi et al, 2023;Zhang et al, 2019). For example, spermatozoa-borne or microinjected miR-34c enhances the development of early embryos in humans, cows, rabbits, and mice (Cui et al, 2023). We hypothesize that more dense stallion spermatozoa carry a population of miRNAs that reflects their superior ability to produce healthy embryos compared to less dense spermatozoa.…”
Section: Introductionmentioning
confidence: 87%
“…However, spermatozoa from bulls with higher fertility have lower concentrations of miR-34c than spermatozoa from bulls with lower fertility (Fagerlind et al, 2015;Kasimanickam et al, 2022). In human, cow, rabbit, and mouse species, sperm-borne or microinjected miR-34c enhances embryo development (Cui et al, 2023). A mouse study determined that a double knockout of both miR-34c and miR-449a…”
Section: Galnt7mentioning
confidence: 99%
“…The expression of miR-34c in sperm correlates with embryonic development kinetics and clinical outcomes. Therefore, miR-34c holds promise as a potential indicator of IVF success and can provide valuable insights into embryonic development ( 140 ). A previous study demonstrated that the expression of miR-34c,-140,-21, and -375 in fresh sperm was lower in patients undergoing IVF with an average embryo score <8 than in those with an embryo score >8.…”
Section: Potential Of Mirnas As Biomarkers For Disease Diagnosis and ...mentioning
confidence: 99%